Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1469-7580.2006.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural features of neurons and synaptic contacts in the posterodorsal medial amygdala of adult male rats

Abstract: The aim of the present study was to describe the ultrastructure of neurons (from eight animals) and to analyse the synaptic terminal distribution (from two animals) in the posterodorsal subnucleus of the medial amygdala (MePD) of adult male rats. Using transmission electron microscopy, it was possible to identify many spiny and aspiny dendrites, unmyelinated axonal bundles, single axonal processes, a few myelinated axons, blood vessels and glial processes in the neuropil. Axodendritic synapses were the most fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…The general ultrastructural appearance of the MePD neuronal perikarya is similar to that described previously for adult male rats (Hermel et al, ). However, we found that the MePD cell bodies had glial processes in close apposition to the perikaryal membrane, some with evident continuous glial processes covering the perikarya whereas others were intermingled among axons (Figs.…”
Section: Resultssupporting
confidence: 83%
“…The general ultrastructural appearance of the MePD neuronal perikarya is similar to that described previously for adult male rats (Hermel et al, ). However, we found that the MePD cell bodies had glial processes in close apposition to the perikaryal membrane, some with evident continuous glial processes covering the perikarya whereas others were intermingled among axons (Figs.…”
Section: Resultssupporting
confidence: 83%
“…Dendritic spines are the structural correlates of learning and memory that regulate synaptic plasticity through dynamic changes in connectivity that are intimately dependent on changes in dendritic arborization (Yoshihara et al 2009). While some controversy exists regarding the precise function of specific spine types (Hermel et al 2006; Urbanska et al 2012), recent evidence suggests that thin spines are more plastic and involved in learning, while mature spines play a larger role in memory (Bourne and Harris 2007). Changes in morphology or spine density that adversely impact synaptic function have been found to compromise neurotransmission and behavioral performance (Matsuzaki et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Most spines showed synaptophysin puncta close to their head and neck, but some spines were not labeled or were characterized by multiple puncta [84]. Although ultrastructural data suggest that dendritic spines usually receive one asymmetrical synapse with round electron-lucent and dense core vesicles [103], inhibitory and multisynaptic contacts have also been found on the dendritic spines of adult male MePD [2].…”
Section: Morphological Features Of the Medial Amygdalamentioning
confidence: 99%